PERANAN BPUPKI DAN PPKI DALAM MEMPERSIAPKAN KEMERDEKAAN INDONESIA1 (Forum Ilmu Sosial, 2009)
Unlike neighboring nations who were given independence by the colonial, Indonesia gainedindependence with the struggle and sacrifi ce. Not only drops of sweat, tears, sacrifi ce property, but alsosports and the lives of the martyrs nation dedicated to the sacred purpose of independent Indonesia. Thanksto the greatness of soul of the characters and PPKI BPUPKI, Indonesia can achieve its independence onAugust 17, 1945. Indonesia’s independence was at later stages become valuable capital for the nation ofIndonesia in Indonesia fi nalizing an independent state, sovereign, just, and prosperous, and to defend thesovereignty of a foreign power undermining.Key words: BPUPKI, PPKI, Independence of Indonesia.